Observation of a multichannel interdigital H-structure - Gavrilov, N.M.; Bogachenkov, D.A.; Komarov, D.A.; Makeyev, A.E.; Strukov, Y.N. (Вопросы атомной науки и техники, 2006)
The paper presents the experimental results together with their comparison with calculations. The relation between
a bunch charge in accelerating channel and a variation of resonant wave-length at asymptotic alternatingphase
focusing is derived. Suggested is also a new way for computation of high-frequency characteristics of the accelerating
structure taking into account the variation of resonant frequency with constant transversal dimensions of
the structure. Приведены результаты эксперимента, сравнение полученных данных с расчетными величинами. Получено выражение зависимости заряда сгустка в ускоряющем зазоре от изменения резонансной длины волны для ассиметричной фазопеременной фокусировки. Приведены результаты нового способа расчета ВЧ-параметров предложенной структуры с учетом фактора изменения длины волны при постоянстве поперечных размеров ускоряющей структуры. Наведені результати експерименту, порівняння отриманих даних з розрахунковими величинами.
Отримано вираження залежності заряду згустку в прискорювальному зазорі від зміни резонансної довжини
хвилі для асиметричного фазозмінного фокусування. Наведено результати нового способу розрахунку ВЧ-
параметрів запропонованої структури з урахуванням фактора зміни довжини хвилі при сталості поперечних
розмірів прискорювальної структури.